Pendampingan Gizi Dan Monitoring Pelaksanaan Minum Bersama Jus Varian Buah Dan Sayur (Di Panti Perlindungan Dan Rehabilitasi Sosial Lanjut Usia (Pprslu) Martapura Dan Landasan Ulin) - Abdurrachim, Rijanti; Widiastuti Hariati, Niken; Ramie , Agustin (JURNAL RAKAT SEHAT (JRS) : Pengabdian Kepada Masyarakat, 2024)
Panti Perlindungan dan Rehabilitasi Sosial Lanjut Usia (PPRSLU) Budi Sejahtera in Banjarbaru and Martapura is one of the implementation units of the South Kalimantan Provincial Social Service which in its activities provides social services to the elderly. These social institutions are located in two areas with the same management, namely in Martapura and in Landasan Ulin Banjarbaru. There are 70 elderly people in Martapura and 140 elderly people in Landasan Ulin Banjarbaru with 4 managers. Disease data from the clinic shows that hypertension always occupies the top 3 most common diseases every month. This community service activity by providing assistance and monitoring and evaluating the results of activities to make fruit and vegetable juices by nutritionists as well as nutrition education, and measuring blood pressure by the Banjarmasin Polytechnic team in Banjarbaru.The results of the juice making assistance activities and juice giving activities can be carried out and can monitor directly or indirectly the independent activities of giving fruit and vegetable juices. The results of this activity received a positive response to be continued as a program from the orphanage. Suggestions for the sustainability of the program to be continued continuously need to be planned for the addition of existing jurumasak personnel, so that nutritionists can consistently carry out the full duties and functions of nutritionists, especially in implementing the program of providing fruit and vegetable juices to the elderly. Keyword : Fruit and vegetable juices, blood pressure control, mentoring and monitoring, nutrition education.